Efeitos adversos do uso de imiquimod no tratamento de lesões da mucosa oral - revisão sistemática - Morais, Anne Diollina Araújo (2023)
Imiquimod (IMI) is a topical chemotherapy with indirect antiviral and antitumor properties used successfully in the treatment of genital warts, actinic keratoses and superficial basal cell carcinoma. Despite its restricted use in the oral cavity, this chemotherapy drug has been used in some conditions that affect the oral mucosa. However, this use has led to some occurrences, such as serious adverse effects. In general, due to its powerful immunomodulatory action, adverse effects of greater comorbidity can be observed regarding its use, regardless of whether it is used in the oral cavity or not. Therefore, the present work has the general objective of evaluating the use of IMI in oral mucosa, and the following specific objectives: 1) Carry out a systematic review to evaluate the adverse effects of the use of IMI on the oral mucosa; 2) Assess whether adverse effects are related to the location applied; 3) Assess whether adverse effects are related to the frequency of application; 4) Assess whether adverse effects are more serious in any condition pathology of the specific oral cavity. This systematic review was registered in the PROSPERO database and the search strategy was carried out in seven databases, including gray literature. After applying all eligibility criteria, 13 studies were selected. The cases were evaluated regarding the clinical characteristics of the patient (sex and age), the lesion to be treated with IMI (location and type of lesion) and the IMI use protocol (dosage and pharmaceutical form, method of application, adverse effects and completion of treatment). In general, IMI causes serious adverse effects when applied to the oral mucosa, especially in the lip vermilion region. Although IMI is considered a successful chemotherapy drug, its oral use should be cautious, due to the lack of standardization of form and frequency of use and the reactions that may be caused.